Nature, particularly the insect fauna of Ladoga and Olonets Karelia - Pekkarinen, Antti; Huldén, Larry (Entomologica Fennica, 1995)
The geology, vegetation, entomological studies, postglacial immigration of insects and characteristics of the insect fauna in southern Russian Karelia are reviewed, with examples of eastern and southern plant and insect species recorded in Russian Karelia, but not recorded or recorded to very limited extent in southern Finland. The management of forests and agriculture in Russian Karelia have been, during the Soviet period much less effective, and thus habitats have retained more diversity than in southern Finland. Recent studies indicate that many species considered threatened in Finland occur abundantly in Russian Karelia.